Household Problems In The Novel Gone Girl By Gillian Flynn - Ema Rosita; Sudirman Maca; Andi Tenri Abeng (Humaniora: Journal of Linguistics, Literature, and Education, 2022)
This study aims to find out the factors and causes of household problem that portrayed in the novel Gone Girl by Gillian Flynn. This research is expected to be a reference for future researchers. The data source used in this research is the novel Gone Girl. In analyzing the data, the researcher applied qualitative descriptive method through a sociological approach. The data were obtained by reading, identifying, note-taking, and quoting techniques. The analysis applied the social context by Ian Watt's theory. The results of this research showed the factors and causes of household problems in the novel Gone Girl by Gillian Flynn is as a reflection of society. Internal factors were factors that came from each partner, how to resolve the conflicts, communicate, and sexual relations, while external factors were factors that from outside the partner such as rude actions against partners, rude words, the presence of other people in household relationships, problems about children, and parental intervention. The cause of household problems was the cause of an event that gave rise to something such as the occurrence of rudeness, cheating, and incompatibility.